Molecular markers of risk of subsequent invasive breast cancer in women with ductal carcinoma in situ: protocol for a population-based cohort study - Joseph A Sparano; Fergus J Couch; Robert T Greenlee; Xiaonan Xue; Yihong Wang; Thomas E Rohan; Mindy Ginsberg; Heather S Feigelson; Stacey Honda; Azadeh Stark; Dhananjay Chitale; Maja H Oktay; et al. (BMJ Open)
Introduction Ductal carcinoma in situ (DCIS) of the breast is a non-obligate precursor of invasive breast cancer (IBC). Many DCIS patients are either undertreated or overtreated. The overarching goal of the study described here is to facilitate detection of patients with DCIS at risk of IBC development. Here, we propose to use risk factor data and formalin-fixed paraffin-embedded (FFPE) DCIS tissue from a large, ethnically diverse, population-based cohort of 8175 women with a first diagnosis of DCIS and followed for subsequent IBC to: identify/validate miRNA expression changes in DCIS tissue associated with risk of subsequent IBC; evaluate ipsilateral IBC risk in association with two previously identified marker sets (triple immunopositivity for p16, COX-2, Ki67; Oncotype DX Breast DCIS score); examine the association of risk factor data with IBC risk.Methods and analysis We are conducting a series of case–control studies nested within the cohort. Cases are women with DCIS who developed subsequent IBC; controls (2/case) are matched to cases on calendar year of and age at DCIS diagnosis. We project 485 cases/970 controls in the aim focused on risk factors. We estimate obtaining FFPE tissue for 320 cases/640 controls for the aim focused on miRNAs; of these, 173 cases/346 controls will be included in the aim focused on p16, COX-2 and Ki67 immunopositivity, and of the latter, 156 case–control pairs will be included in the aim focused on the Oncotype DX Breast DCIS score®. Multivariate conditional logistic regression will be used for statistical analyses.Ethics and dissemination Ethics approval was obtained from the Institutional Review Boards of Albert Einstein College of Medicine (IRB 2014-3611), Kaiser Permanente Colorado, Kaiser Permanente Hawaii, Henry Ford Health System, Mayo Clinic, Marshfield Clinic Research Institute and Hackensack Meridian Health, and from Lifespan Research Protection Office. The study results will be presented at meetings and published in peer-reviewed journals.